Case report: ‘Atypical Richter transformation from CLL-type monoclonal B-cell lymphocytosis into Burkitt lymphoma in a treatment naïve patient’ - Jauch, Annaïse J.; Alborelli, Ilaria; Reusser, Andreas; Baschong, Albert; Rütsche, Cyrill; Bignucolo, Olivier; Passweg, Jakob; Dirnhofer, Stefan; Krasniqi, Fatime (Frontiers in Oncology, 2024)
Background: Richter transformation refers to the progression of an initially slow-growing small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL) into an aggressive lymphoma, typically diffuse large B-cell lymphoma (DLBCL) or Hodgkin lymphoma.Case presentation: The patient presented with a rapid onset of localized cervical swelling, accompanied by monoclonal B-cell lymphocytosis displaying a CLL immunophenotype. The histopathological analysis identified a Burkitt lymphoma (BL) located in the submandibular gland and adjacent lymph node. The patient's bone marrow displayed a minor infiltration of monoclonal B-cells with a CLL immunophenotype (< 10%). Molecular analysis demonstrated the presence of the same monoclonal rearrangement in the framework region (FR3 region) of the immunoglobulin heavy chain (IGH) locus.High-throughput sequencing of the immunoglobulin heavy and light chains also confirmed the presence of the same rearrangement in SLL/CLL and in the Burkitt lymphoma sample, but also highlighted the presence of a second rearrangement in the Burkitt lymphoma cells, not shared with the SLL/CLL cells in the bone marrow.The patient was treated with DA-EPOCH-R, which lead to a complete metabolic response.This report provides an exceptionally rare description of a CLL-type monoclonal B-cell lymphocytosis transforming into a very aggressive Burkitt lymphoma in a treatment naïve patient.Richter transformation refers to the progression of an initially slow-growing small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL) into an aggressive lymphoma, typically diffuse large B-cell lymphoma or Hodgkin lymphoma.This report provides one of the first descriptions of a CLL-type monoclonal B-cell lymphocytosis transforming into a very aggressive Burkitt lymphoma, supported by high-throughput sequencing of the B-cell receptor, which demonstrated the presence of the same monoclonal rearrangement in the immunoglobulin heavy chain locus in the bone marrow and submandibular gland. Additionally, the Burkitt lymphoma cells displayed a second co-dominant rearrangement in the IGH.The patient was treated with systemic chemotherapy and both malignancies were not detectable after the treatment.